Development of Audio Denoising. - Rush, David (My University, 2009)
An audio denoising plug-in for the very widely used audio processor, Audacity, was developed and tested on many noisy musical recordings. Our new method outperforms Audacity's own built-in denoiser. We then worked on adapting our denoising method to produce a real-time audio denoiser for an embedded hardware device.
Color poster with text and images.
Keywords: Denoising; Noise control--Computer programs; Acoustical engineering--Computer programs; Signal processing--Computer programs; Posters